The Analysis of Sustainability Balanced Scorecard To Measure The Company Performances ( A Case Study On PT Gagas Energi Indonesia ) - Febriyanti, Kartika; Sukoharsono, Eko Ganis (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to analyze the performance appraisal of PT Gagas Energi Indonesia by using the concept of Sustainability Balanced Scorecard method. Sustainability Balanced Scorecard is a modification of the conventional Balanced Scorecard that have their own uniqueness which this method will be focusing exclusively assessment of the environmental and social aspects that are sometimes not considered by the company to run the business. Companies that use methods of sustainability balanced scorecard as a tool to measure the performance of the company, certainly capable of running even find the right strategy for their businesses when the company was facing a problem. To collect the data, the researcher, uses open ended questionnaires to 10 respondents consist of 5 employees and 5 customers of PT Gagas Energi Indonesia. The instrument of the questionnaires consist of financial perspective, customers perspective, internal business process perspective, learning and growth perspective, and sustainability balanced scorecard. The results of this study illustrate the good results and can indicate a pretty good number for each ratio or factor ratings in each perspective. However, pretty good is can not Â a guarantee that the strategy used by the company was good. The company should continue to make a further assessment using the method of Sustainability Balanced Scorecard to get a much better value than before. Sustainability Balanced Scorecard would be better if done by considering the factors contained in the perspective of sustainability, especially environmental and social factors.Key word: Performance Assessment, Balanced Scorecard, Perspective, Sustainability factors, Sustainability Balanced Scorecard.